2019
DOI: 10.3390/su11154192
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Grey Systems Theory-Based Methods and Applications in Analyzing Socio-Economic Systems

Abstract: The present study seeks to provide an overview of studies dealing with the grey systems theory from the perspective of socio-economic systems. A scoping review is conducted to explore the studies focusing grey systems theory and its applications in socio-economic systems. The publications selected for analysis were collected through searching the databases of the Web of Science, Scopus, and Science Direct. The publications were selected from 2010 to 2019, and the following keywords were used to detect them: gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…On the other hand, the literature points to the use of holistic approaches and GST-based methods of system thinking, which can help achieve better results in the analysis of socio-economic systems. The Grey Systems Theory and related methods can be a very attractive, practical and appropriate way of solving social and economic problems [25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the literature points to the use of holistic approaches and GST-based methods of system thinking, which can help achieve better results in the analysis of socio-economic systems. The Grey Systems Theory and related methods can be a very attractive, practical and appropriate way of solving social and economic problems [25].…”
Section: Resultsmentioning
confidence: 99%
“…In the paper [25], the authors focused on the problem of adequacy of the application of methods included in the theory of grey systems in modeling uncertainty in socio-economics systems. The main conclusion from the analyses was that the possibility of using data that are few, incomplete and subjective, makes GST an adequate tool for modeling systems whose key element is the human being.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ese improvements have effectively improved the prediction accuracy of the grey model. erefore, the grey model is widely used in energy [19], economic [20], environmental governance [21], and other related research studies. It is worth emphasizing that the advantage of the grey forecasting model compared with other forecasting methods lies in dealing with small sample problems.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of gray theory and the feasibility study of bolting and shotcrete supports, many scholars at home and abroad have elaborated on it in many aspects; researches such as Szpak and Tchórzewska-Cieślak found that the gray theory was widely used in domestic water, infrastructure construction, economic development, etc. [6][7][8]; Lu believed that the gray theory could predict mine water inflow with high reliability and applicability [9]; Harding et al found that bolt support could effectively control surrounding rock deformation, and its support effect was related to bolt parameters [10][11][12]; Forrestde and Liu convinced that the gray theory prediction could grasp real-time problems in tunnel deformation, slope collapse, and surface settlement [13]; Zhou believed that the gray theory could predict the stress change and unknown deformation of tunnel lining [14]; Huo et al believed that the gray prediction was an effective means of predicting tunnel deformation, which could be used as a theoretical support for tunnel construction, design, and support to improve operation efficiency [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%